The Implementation of Character Education Through Islamic Education Learning at SMP PGRI I Bojonegoro - su yati (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Character education is a process of transformation of life values to be developed in the personality of a person or student so it becomes one in the person's life behavior. Character education is not only about teaching what is right and what is wrong, more than that character education inculcate habits about good so students become the wrong idea which one is right, and able to feel good value so students will be able to do good things. This study is aimed to teach the characters values and analyze the obstacles and supporting factors of the character education of students through Islamic Education learning in SMP PGRI I Bojonegoro. Qualitative research method is used in this study, a research method that does not use the count (statistics) but through data collection, analysis and then interpretation. The qualitative descriptive research attempts to describe the situation or events, does not seek or explain the relationship but describes the situation. The research results show that the values taught to students of SMP PGRI 1 Bojonegoro are religious, honesty, democratic, social interest, environmental interest, discipline. The supporting factors of the implementation of character education are the availability of facilities, and proper classroom infrastructure, good student learning interests, comfortable class atmosphere, and clean classroom. Keywords: Character Education, Islamic Education Subject